2010
DOI: 10.1534/genetics.110.117234
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functions for Drosophila Mcm10 Suggested Through Analysis of Two Mcm10 Mutant Alleles

Abstract: DNA replication and the correct packaging of DNA into different states of chromatin are both essential processes in all eukaryotic cells. High-fidelity replication of DNA is essential for the transmission of genetic material to cells. Likewise the maintenance of the epigenetic chromatin states is essential to the faithful reproduction of the transcriptional state of the cell. It is becoming more apparent that these two processes are linked through interactions between DNA replication proteins and chromatin-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 56 publications
6
49
0
Order By: Relevance
“…Co-immunoprecipitation studies in human cells and Xenopus egg extracts have demonstrated that Mcm10, Pol-α and Ctf4 are in a common complex and postulated that Mcm10 and Ctf4 connect the lagging strand polymerase, Pol-α, with the CMG helicase [38]. This notion is consistent with the finding that genetic disruption of Mcm10 and knockdown of Ctf4 result in very similar cellular phenotypes in Drosophila melanogaster [42, 43]. Moreover, depletion of either Ctf4 or Mcm10 has been implicated in regulating the turnover of Pol-α [5, 38, 44, 45].…”
Section: Structure and Function Of Mcm10supporting
confidence: 68%
“…Co-immunoprecipitation studies in human cells and Xenopus egg extracts have demonstrated that Mcm10, Pol-α and Ctf4 are in a common complex and postulated that Mcm10 and Ctf4 connect the lagging strand polymerase, Pol-α, with the CMG helicase [38]. This notion is consistent with the finding that genetic disruption of Mcm10 and knockdown of Ctf4 result in very similar cellular phenotypes in Drosophila melanogaster [42, 43]. Moreover, depletion of either Ctf4 or Mcm10 has been implicated in regulating the turnover of Pol-α [5, 38, 44, 45].…”
Section: Structure and Function Of Mcm10supporting
confidence: 68%
“…Therefore, the two proteins might affect Mcm2 in alternative ways, with Cdc45 closing the gate to support helicase activity, and Cdt1 allowing opening and closing of the gate during MCM2-7 loading. Moreover, Mcm10 might affect these surfaces as well, as it contacts the Mcm2 NTD (Apger et al 2010;Lee et al 2010;Looke et al 2017) in order to stabilize the CMG complex (Looke et al 2017). At an in vitro assembled replication fork, ssDNA appears from the N-terminal MCM2-7 face during DNA unwinding (Georgescu et al 2017).…”
Section: N-terminal Interactionsmentioning
confidence: 99%
“…Furthermore, spMcm10 has been reported to stimulate DDK phosphorylation of Mcm2-7 (Lee et al 2003), and is thus believed to play a role in helicase activation. Studies in S. cerevisiae have shown that scMcm10 facilitates assembly of the Cdc45/Mcm2-7/GINS helicase complex (Gambus et al 2009), and physical interactions have been observed with Mcm2, Mcm4, Mcm5, Mcm6, and Mcm7 subunits (Apger et al 2010; Hart et al 2002; Homesley et al 2000; Merchant et al 1997). Recent work suggested that scMcm10 serves as a functional linker between the MCM helicase and pol α by coordinating their activities and ensuring their physical stability and integrity at the replication fork (Lee et al 2010), a role also identified for Ctf4 (Gambus et al 2009).…”
Section: 2 Role Of Mcm10 In Replicationmentioning
confidence: 99%